More effective organics removal by amorphous MnOx assisted by micro-current than peroxymonosulfate addition: Performance and mechanism. Issue 3 (June 2022) - Shi, Xinxin; Cao, Chi; Guo, Pengfei; Wen, Gang; Lu, Zheng; Shi, Julian; Peng, Dangcong; Huang, Tinglin
Abstract: Peroxymonosulfate (PMS) addition into a MnOx system is generally believed to be an effective way for expediting organics removal. Whereas in this work, we found single MnOx with a micro-current got an even better oxidation performance comparing that with PMS addition. The carbon paper electrodeposited by amorphous MnOx (AMO) was used as cathode, and the micro-current (55 µA/cm 2 ) increased the methylene blue (MB) degradation rate by 6.1 times through enhancing the AMO oxidative ability in acidic media. At the same pH, the MB degradation rate in AMO (AMO-MC) system was close to that in AMO system with PMS addition (AMO-MC-PMS). More importantly, the MB mineralization in AMO-MC was about 1.6 times higher than that in AMO-MC-PMS. Similar phenomena were also investigated when using tetracycline (TC) as organic pollutant. The mechanisms of AMO-MC and AMO-MC-PMS for MB removal were comprehensively studied and compared. It was found that the micro-current prompted the Mn valence converting from high to low. Conversely, the PMS addition hindered this converting and impeded the direct oxidation of AMO. The GC-MS analysis indicated that the presence of PMS induced the formation of sulfoxide-containing intermediates (SCIs) which were difficult to be further degraded and resulted in the suppression of MB mineralization. Density functional theory (DFT) calculation indicated that the intermediates from AMO-MC were more facile to be attacked in an electrophilic way and adsorbed on the cathode than the SCIs. It proposed that the AMO with micro-current had the potential to remove organics efficiently, and blind PMS addition should be avoided. Graphical Abstract: ga1 Highlights: Amorphous MnOx (AMO) system can remove MB efficiently with the aid of a cathodic micro-current. The micro-current can improve the activity of AMO system better than peroxymonosulfate (PMS). Single AMO system got mineralization of 30% higher than the AMO-MC-PMS system. Refractory intermediates were generated in the AMO-MC-PMS system. PMS may not always play a positive role and blind addition should be avoided.